Indios nobles, mala mezcla, chinos vagantes: representaciones en el perú del siglo XVIII - Elena Altuna (Centre de Recherches sur les Mondes Américains, 2008)
The documents analysed and compared here correspond to the conflictive times of Peru's 18th century. Two periods are particularly relevant: the government of viceroy Castelfuerte (1724-1736), and Tupac Amaru II's rebellion. The selection responds to common patterns concerning the pragmatic nature of the texts, as they all exposed the evils of the system to the monarch, and propose the means to overcome them. Here, ‘representations’ and ‘arbitrary’ writings are representative of the social struggles of the troubled context in which they appeared. In the analysis, text sources representing certain groups are studied in relation to the positions sustained by other sectors, bearing in mind that in the generation of identity-based alliances, fear is always a significant factor.